2021
DOI: 10.15294/edaj.v10i3.45456
|View full text |Cite
|
Sign up to set email alerts
|

Does Monetary Transmission Effective? Evidence from Indonesia

Abstract: This study aims to examine the effects of monetary policy in Indonesia on real variables represented by output and nominal variables represented by inflation. This research is based on an autoregressive distributed model (ARDL) approach which includes lag for the dependent variable and its explanatory variables as regressors. So it is appropriate to analyze time-series data dynamically. Monetary policy variables include deposit interest rate, lending interest rate, asset/stock price, and exchange rate. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Despite its use as a countercyclical tool to stimulate economic growth, monetary policy can also lead to an increase in prices due to an increase in money supply. This outcome is consistent with the findings of previous studies (Arintoko & Kadarwati, 2022;Nyumuah, 2018;Abbasinejad et al, 2018;Sethi et al, 2019;Mandel et al, 2019;Arintoko, 2021;Tai Nguyen et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite its use as a countercyclical tool to stimulate economic growth, monetary policy can also lead to an increase in prices due to an increase in money supply. This outcome is consistent with the findings of previous studies (Arintoko & Kadarwati, 2022;Nyumuah, 2018;Abbasinejad et al, 2018;Sethi et al, 2019;Mandel et al, 2019;Arintoko, 2021;Tai Nguyen et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…The relationship between economic growth and monetary policy, specifically the role of policy interest rates, was extensively examined by (Arintoko & Kadarwati, 2022) using the VAR method, which showed that policy interest rates respond positively to unexpected GDP changes. Previous studies have suggested that monetary policy plays a crucial role in regulating economic growth, inflation, and exchange rates (Nyumuah, 2018); (Abbasinejad et al, 2018); (Sethi et al, 2019); (Mandel et al, 2019) (Arintoko, 2021); (Tai Nguyen et al, 2022). (Kim & Lim, 2018) and (Kim et al, 2020) note that monetary policy shocks can affect exchange rates.…”
Section: Theoretical Reviewmentioning
confidence: 99%